The Development of Three Tier Multiple Choice Test to Explore Junior High School Students’ Scientific Literacy Misconceptions (Journal of Innovative Science Education, 2019)
Misconceptions of students scientific literacy can be overcome by knowing in advance the alternative concepts students have. One technique that can be used to trace students misconceptions is using multiple choice diagnostic tests. This research aim was developing three tier multiple choice test based on aspects of scientific literacy in science material. We used Research and Development (R&D) as the research method. The phase of method implementation analysis, design, development, implementation, and evaluation (ADDIE). The results of the study showed that the product of this research was 37 items three tier multiple choice test based on scientific literacy aspect. The product were developed in a reliable and valid category with a reliability value of r11>rtabel is 1,024>0,3061 and each expert give a validity score of 16, 13 and 14. Characteristics of items with difficulty levels mostly in the medium category. The distinguishing features in most categories is accepted. Each item is arranged based on aspects of scientific literacy with a comparison category A: B: C: D: E is 35%: 20%: 20%: 17.5%. Profil of misconceptions of scientific literacy the proportion of about 35,1 % knowledge aspect, 34,8 % about the competence in the investigation, 33 % about the science as a way of thinking, and 31,4 % about the science relations with technology, society, and the environment as a context and attitude to science. The results of developing this question can be used as teacher as an alternative item to identify misconceptions in students' scientific literacy.